2007
DOI: 10.1177/0363546507305098
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Scapular Upward Rotation between Baseball Pitchers and Position Players

Abstract: This decrease in scapular upward rotation may compromise the integrity of the glenohumeral joint and place pitchers at an increased risk of developing shoulder injuries compared with position players. As such, pitchers may benefit from periscapular stretching and strengthening exercises to assist with increasing scapular upward rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…The inclinometer was modified by attaching 2 wooden palpation dowels to the bottom of the instrument. 8,11,28,35 Upward/downward rotation of the scapula was measured relative to horizontal by aligning the indented Y of each palpation dowel along the medial and lateral aspect of the scapular spine (FIGURE 1). 8,11,37 Prior research has indicated that measurement of scapular upward/ downward rotation with a modified digital inclinometer is a reliable procedure.…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclinometer was modified by attaching 2 wooden palpation dowels to the bottom of the instrument. 8,11,28,35 Upward/downward rotation of the scapula was measured relative to horizontal by aligning the indented Y of each palpation dowel along the medial and lateral aspect of the scapular spine (FIGURE 1). 8,11,37 Prior research has indicated that measurement of scapular upward/ downward rotation with a modified digital inclinometer is a reliable procedure.…”
Section: Instrumentationmentioning
confidence: 99%
“…8,11,28,35 Upward/downward rotation of the scapula was measured relative to horizontal by aligning the indented Y of each palpation dowel along the medial and lateral aspect of the scapular spine (FIGURE 1). 8,11,37 Prior research has indicated that measurement of scapular upward/ downward rotation with a modified digital inclinometer is a reliable procedure. 8,11 A priori reliability testing of 15 healthy participants, tested twice over a 48-hour period, was performed by the principal investigator.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…1,9,[22][23][24][25] Several studies have demonstrated alterations in scapular position or motion in injured and healthy overhead athletes. 8,9,19,26 These studies have commonly observed decreased amounts of scapular upward rotation, 8,9,19,27 which is thought to decrease the subacromial space by approximating the acromion with the humerus. However, this relationship has yet to be determined in healthy college baseball players.…”
Section: Discussionmentioning
confidence: 99%